Invitro Fermentation of West African dwarf (wad) goats fed treated Rice husk as Wheat bran substitute: Invitro Fermentation of West African dwarf (wad) goats fed treated Rice husk as Wheat bran substitute - Femi, Afolayan (BADEGGI JOURNAL OF AGRICULTURAL RESEARCH AND ENVIRONMENT, 2023)
ABSTSRACT The study was conducted to evaluate the in vitro fermentation characteristics of West African Dwarf goat fed treated rice husk as wheat bran substitute. A total of 20 growing West Africa Dwarf goats were subjected to five dietary treatments in a completely randomized design with 4 animals per replicate. The treatments are: 0% RH (T1), 25% RH (T2), 50% RH (T3), 75% RH (T4) and 100% RH (T5). The animals were fed at 5% of their body weight. The result showed that T2 and T1 are relatively high in crude protein, low in crude fiber, moderate in crude fat and high in carbohydrate. They equally had the lowest values of ADF, ADL and NDF among the treatments. The gas volume produced under each treatment continue to increase at every three hours. The production of gas was significantly (P<0.05) influenced by the incubation period and that T1 produced more gas followed by treatment T2 and then T3 and T4 while T5 had the least gas production. Methane (CH4) production was least in goats fed T4, followed by goat fed T1 while those on T2, T3 and T5 produced the highest and same methane gas quantities. In conclusion, treated rice husk as a substitute for wheat bran at 25 and 75% inclusion level gave better in-vitro fermentation performance in the goat. Key words: Treated rice husk, WAD goat, weigh gain, feed conversion ratio, feed intake